A MULTIPLE SCATTERING MODEL FOR THE ATMOSPHERE-SNOW SYSTEM - アオキ, テルオ; AOKI, Teruo (National Institute of Polar Research, 1992)
P(論文) A multiple scattering model for radiative transfer in the atmosphere-snow system is constructed by applying the Mie theory to the snow layer composed of ice grain particles. The spectral albedo from 0.2 to 3.0μm wavelength is examined as a function of effective grain size, solar zenith angle and snow optical depth with the single snow layer model. The upward radiances at the top and base of the atmosphere are also examined with the single atmospheric layer + single snow layer model. The spectral variation of albedo is mainly dependent on the imaginary part of the refractive index of ice. The albedo decreases at all wavelengths with increase of grain size; its degree is generally large in the infrared region and small in the visible region. The albedo increases with increase of solar zenith angle and optical depth of snow. These results are consistent with previous work. The upward radiance distribution in the solar principal plane shows that snow reflectance gradually deviates from the Lambertian with the increase of solar zenith angle. departmental bulletin paper